Role of dutasteride (5-alpha-reductase inhibitor) in patients undergoing transurethral resection of prostrate - Koul, Shafeen Majid; Shah, Imtiaz; Khurshid, Omer; Koul, Shehwar Majid; Shah, Momin (International Journal of Research in Medical Sciences, 2018)
Background: Bladder outflow obstruction due to benign prostate hyperplasia is the commonest urological condition affecting men over 50 years of age. Medical therapy is usually the first line management of BPH. The most frequent complication is encountered is perioperative bleeding and postoperative bleeding. Preoperative use of 5-alpha-reductase inhibitors like dutasteride to reduce surgical bleeding is still a topic of debate. The aim of this study was to evaluate whether pretreatment with dutasteride for 4 weeks prior to surgery can reduce surgical blood loss as well as post op blood loss and complications. Methods: A total of 60 patients with BHP who were to undergo TURP were enrolled and randomized into 2 groups. The dutasteride group consisted of 30 patients who were treated with dutasteride (0.5mg) for 4 weeks before surgery and the control group consisted of 30 patients. Results: The preoperative hemoglobin levels of cases and controls was done followed by postoperative hemoglobin. The average fall in hemoglobin was 0.9mg/dl in cases and 2.1mg/dl in controls. Concluding that group of patients taking dutasteride (cases) peri and post-operative surgical bleeding was significantly reduced on pretreatment of dutasteride for 4 weeks before TURP. Conclusions: Many other surgical treatments are being developed for BHP, but TURP is the gold standard treatment. However, morbidity and blood loss are major potential complications and taking dutasteride 4 weeks prior to transurethral resection of prostrate can be effective in reducing its complications.